The Effectiveness of Reading Comprehension Strategies - Kwabi, Sharon (My University, 2014)
This study examined the underlying cognitive processes of high and low working memory (WM) individuals, how these processes are affected by test presentation and how comprehension performance is affected by the various interactions (Rapp et al, 2007). Ninety college students performed the Nelson Denny Reading Test with an eye tracker. Test presentation was in the concurrent (passage accessible during question answering) and in the sequential (passage inaccessible during question answering) formats. It was predicted and found that participants in the concurrent did better than those in the sequential format. Participants also took the Operation Span Task to measure their WM and it was predicted and found that participants with high WM performed better than those with low WM. This study also aimed to highlight whether high level (re-reading the text) or low level (word recognition) processes were used by different WM individuals and found that high WM used more high level processing and low WM used more low level processing. The study had implications for test takers to be more aware of their WM abilities in order to excel at reading comprehension by using strategies that address their weaknesses.
Keywords: college students; working memory; reading comprehension; strategies